Project Management of a Research Internship in Medical Applications - Simona COSTACHE; Mihaela-Elena ULMEANU; Cristian-Vasile DOICIN; Paulina SPÂNU (Communications of International Proceedings, 2020)
Design and development of medical applications often require a multidisciplinary approach in order to accurately identify the specific needs of customers. Due to the complexity and multiplicity of knowledge and information sources, a structured approach to product design and development of medical applications brings several advantages, specific to the research area, amongst which: standardisation and regulation of preoperative and postoperative medical care of patients, improvement in patient compliance, more accurate medical training materials and devices. The purpose of the current paper is to present in detail a methodology for management and implementation of a research internship as a project that brings together knowledge and competences acquired in medical applications design. The research internship was undertaken within an academic context and environment, based on a structured approach and it applies the basic principles of project management such as project initiation—defining the problem, determining project feasibility by research, planning-monitoring-control, execution and evaluation. This research paper summarizes the background and the purpose of the research internship, describes the process and the methods used to accomplish the tasks by defining the resources, calendar, activity plan and by evaluating the final results at the end of the process.
Keywords: Project Management; Medical Applications; Mandible; 3D Printing.